The Influence Of Influencer Communication Strategies On Audience Donation Participation (A Study Of Windah Basudara’s Charity Live Streaming) - Salfhaoctha Friemay Aliefia Poetry; Tri Satria Muhammad; May Rizdiana Santi; Ferdi Setiawan (Jurnal Ilmiah Multidisiplin, 2026)
The development of digital media, particularly live streaming, has led to new forms of social fundraising that utilize influencers as key communicators. One prominent phenomenon is the success of Windah Basudara, an Indonesian gaming content creator, in raising a substantial amount of donations through live streaming activities. This phenomenon highlights the importance of communication strategies in encouraging audience donation participation. This study aims to analyze the effect of communication strategies on audience donation participation in live streaming based fundraising activities conducted by Windah Basudara. This research adopts a positivist paradigm with a quantitative approach and a survey method. Data were collected through online questionnaires distributed via Google Forms to 100 respondents selected using probability sampling. Communication strategies were measured based on the five dimensions of Lasswell’s communication model communicator, message, media, audience, and effect while donation participation was measured through financial, affective, interactive, social, and cognitive dimensions. Data were analyzed using inferential statistics with multiple linear regression analysis. The results indicate that communication strategies have a positive and significant effect on audience donation participation. Effective communication strategies characterized by communicator credibility, clear and transparent messages, interactive use of live streaming media, and alignment with audience characteristics can enhance audience engagement in donation activities. These findings confirm the crucial role of communication strategies in the success of digital-based social fundraising.